Business Communication Strategies: Analysis of Internal Communication Processes - Ali, Bayad Jamal; Anwar, Govand; Gardi, Bayar; Othman, Baban Jabbar; Aziz, Hassan Mahmood; Ahmed, Shahla Ali; Hamza, Pshdar Abdalla; Ismael, Nechirwan Burhan; Sorguli, Sarhang; Sabir, Bawan Yassin (International Journal of Humanities and Education Development (IJHED), 2021)
The purpose of this research is to investigate the current situation of internal communication in the maintenance department in the cement industry. In most organizations, employees and managers have struggled with the thought of attempting to solve weak and bad communication between the two parties which mostly cause issues to an organization, whether in performance or cost wise. This research was carried out at the maintenance department in Cement Company. A quantitative method was used to gather relevant information regarding a study of internal communication in maintenance department in cement industry. The research findings were supported that current management at Cement industry implementing team meetings effectively. The current management at Cement industry is creating and using online- printed communications tools, organizing regular events. The research findings were supported that current management at Cement industry using online tools for internal communication. In terms of notice board communication, the researcher was not able to find any link between company’s’ standard as a fact of internal communication method and respondent’s perception as research findings. At this point the researcher was able to point out the gap between this study and the fact of internal communication at maintenance department in Cement industry. According to the findings the researcher was able to find out the gap between site visit communication between perception and the fact. Concerns of face-to-face communication method, also, was not found in the standard of internal communication at cement industry. Accordingly, the researcher was able to point out the gap between face-to-face communication method as a fact and respondents’ perception according to the research findings. The current management at Cement industry is establishing a regular, transparent communication with all employees covering the entire organization. The research findings were supported that current management at Cement industry implementing network communication effectively.